2005
DOI: 10.1021/jo0511041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hepatic Transport of Strongly Fluorescent Cholephilic Dipyrrinones

Abstract: A new class of highly fluorescent (phi(F) 0.3-0.8) low molecular weight water-soluble cholephilic compounds has been synthesized in two steps from dipyrrinones. The dipyrrinone nitrogens are first bridged by reaction with 1,1'-carbonyldiimidazole to form an N,N'-carbonyldipyrrinone (3H,5H-dipyrrolo[1,2-c:2',1'-f]pyrimidine-3,5-dione) nucleus, and a sulfonic acid group is then introduced at C(8) by reaction with concd H(2)SO(4). The resulting sulfonated N,N'-carbonyl-bridged dipyrrinones ("sulfoglows") are isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Bilirubin (Sigma-Aldrich) containing 6% 4 Z ,15 Z -bilirubin IIIα, 87% 4 Z ,15 Z -bilirubin IXα and 5% 4 Z ,15 Z -bilirubin XIIIα and <2% Z , E isomers (as determined by HPLC) 51 was dissolved immediately before use at 10 mM in dimethylsulfoxide (DMSO) in a foil-wrapped microcentrifuge tube. The bilirubin and HSA solutions were mixed to give a bilirubin to HSA molar ratio of 1.1:1 and 3:1, and incubated with rotation in the dark overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Bilirubin (Sigma-Aldrich) containing 6% 4 Z ,15 Z -bilirubin IIIα, 87% 4 Z ,15 Z -bilirubin IXα and 5% 4 Z ,15 Z -bilirubin XIIIα and <2% Z , E isomers (as determined by HPLC) 51 was dissolved immediately before use at 10 mM in dimethylsulfoxide (DMSO) in a foil-wrapped microcentrifuge tube. The bilirubin and HSA solutions were mixed to give a bilirubin to HSA molar ratio of 1.1:1 and 3:1, and incubated with rotation in the dark overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…They are thus useful in clinical diagnosis as they will appear in urine when hepatic elimination is impaired by cholestatic liver disease. 33…”
Section: As Diagnostic and Therapeutic Agentsmentioning
confidence: 99%
“…4 ) that is taken up by unknown hepatic transport proteins and is excreted into bile by Mrp2 and an Mrp2-independent pathway. 16 The hepatobiliary disposition of this substrate was evaluated in automated SCRH studies, and results consistently showed significant accumulation (cells + bile = 180 ± 27 pmoles/mg protein; cells= 110 ± 9.2 pmoles/mg protein) and a relatively high BEI (41 ± 8.6) in SCRH ( n = 6 ), which are both desirable probe quantities.…”
Section: Resultsmentioning
confidence: 95%
“…[13][14][15] Sulfoglow 1a was selected as a novel substrate to evaluate with automated studies because it is a water-soluble, fluorescent molecule with some structural similarities to bilirubin, and it is rapidly taken up and excreted intact following intravenous injection into rats. 16 Bilirubin and its glucuronide conjugates are well-recognized markers of hepatic dysfunction. 17 Here, we demonstrate the use of the applications described above using SCRH in a fully automated format.…”
Section: Introductionmentioning
confidence: 99%